Evaluation of Nutritive Properties of the Large African Cricket (Gryllidae sp) - Adebowalea, Yemisi A.; Adebowal, Kayode O.; Oguntokunc, Michael O. (Biological Sciences - PJSIR, 2005)
The large African cricket (Gryllidae sp) was subjected to standard analytical procedures to determine its proximate composition, functional properties, amino acids spectrum, in vitro protein digestibility, and nutritionally valuable minerals. The moisture was low (2.13-3.48%), while the protein content was high (65.95%) in the male cricket and 65.11 % in the female cricket). Seventeen amino acids were detected. The essential amino acids contributed 46.1-47.8% of the total amino acid content. Results of the in vitro protein multienzyme digestibility indicated high digestibility (90.7-94.7%) . The amino acids scores were also favourable. The crude fibre and fat contents were fairly high, while the total carbohydrates were low (8.26-12.49%). The carbohydrates fraction contained 85.9-88.0% carbohydrates as stored glycogen. Phosphorus was the highest mineral in the ash (180.92 mg per 100 g) , while the concentration of zinc was the lowest (1.46 mg per 100 g). Copper, manganese, nickel and lead were below the detection limits. Observations on the functional properties revealed low gelation, oil absorption, and emulsion capacity and stability. The effect of pH on the protein solubility showed that the lowest solubility occurred at the pH value of 4.0, while maximum solubility was recorded at the pH values of 6 and 7.